2002
DOI: 10.1006/jmbi.2001.5404
|View full text |Cite
|
Sign up to set email alerts
|

Atomic (0.94 Å) resolution structure of an inverting glycosidase in complex with substrate

Abstract: The crystal structure of Clostridium thermocellum endoglucanase CelA in complex with cellopentaose has been determined at 0.94 A resolution. The oligosaccharide occupies six D-glucosyl-binding subsites, three on either side of the scissile glycosidic linkage. The substrate and product of the reaction occupy different positions at the reducing end of the cleft, where an extended array of hydrogen-bonding interactions with water molecules fosters the departure of the leaving group. Severe torsional strain upon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
144
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(151 citation statements)
references
References 38 publications
7
144
0
Order By: Relevance
“…Glycine molecules are bound on the surface mainly through ionic interactions. 501,502 ) are bound in the deep pocket, which was confirmed to be an active site in ␣ 6 /␣ 6 -barrel enzymes, and is formed by residues belonging to inner helices and long loops (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) (Figs. 2c and 5 atom of its amino group to the Asp 149 O ␦1 atom (2.9 Å).…”
Section: Resultsmentioning
confidence: 94%
“…Glycine molecules are bound on the surface mainly through ionic interactions. 501,502 ) are bound in the deep pocket, which was confirmed to be an active site in ␣ 6 /␣ 6 -barrel enzymes, and is formed by residues belonging to inner helices and long loops (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) (Figs. 2c and 5 atom of its amino group to the Asp 149 O ␦1 atom (2.9 Å).…”
Section: Resultsmentioning
confidence: 94%
“…Although the general catalytic mechanism of inverting glycosidases is known, the transition state and the conformations adopted by the pyranosyl ring of the Ϫ1 sugar are still indefinite. Some reports on the inverting GH8 enzymes suggested that the Ϫ1 sugar ring displays an unfavorable boat 2,5 B conformation (42,43). We have been trying to get insight into the structural changes of the Ϫ1 sugar along the reaction pathway based on the crystal structure of the enzyme-NAG oligomer complexes.…”
Section: Discussionmentioning
confidence: 99%
“…28 Guerin and co-workers published a high-resolution crystal structure, PDB 1KWF, of a mutated (E95Q) GH8 endoglucanase (EG) from the C. thermocellum cellulosome (Figure 2). 25 A cellopentaose molecule is bound in a groove-shaped active site, characteristic of EGs, spanning subsites -3, -2, -1, +1, and +2. The active site forces the cellopentaose chain to kink, and it distorts the glucosyl residue in subsite -1 away from the ground-state 4 C 1 conformation to a 2 S O / 2,5 B ring conformation, while the other four glucosyl residues remain in the relaxed 4 C 1 conformation.…”
Section: Introductionmentioning
confidence: 99%